Estratégias de sustentabilidade e desenvolvimento para o setor da carne bovina - um estudo de caso em um frigorífico de São Gabriel - RS - Oliveira, Rudi Macedo de (2007)
This study describes supportability and development strategies for the bovine meat section in relation to the changes in the atmosphere, through a case study applied to the activities of a slaughterhouse in the south area of the state of Rio Grande do Sul, São Gabriel's city, under the main leader's optics. This work was presented through a qualitative and longitudinal research, through a semi-structured interview with the main director of the company, verifying the last 17 years of the company s activities. Starting from the synthesis of the characteristics of the section and of a chronological analysis of the bovine mea section from the period of 1989 to the current days, describing the current slaughterhouse situation, the report and the organization chart of the company since Vanhove's Family arrival to Brazil, from the beginning of their activities to the current days. Nine identified strategies were described during the studied period, following a chronological order. In each item we defined: opportunities, threats, strategies, analyze of the period and the effects obtained by the company with the use of the strategy. This study stands out in autonomy effects in the production with the construction and structure enlargement to buy cattle for slaugter, slaughtering and distributing bovine meat with own resources, construction of a supermarket with butcher shop, and investment in automation as well as economical effects in certain periods with reduction in the production flow and work day. We recommend studies involving family company, and the investigation of strategies used in other companies linked to the bovine meat section